Effect of Substrate Thickness on Horizontal Magnetoresistance - T. Phetchakul; Y. Chemthung; A. Poyai (My University, 2020)
Abstract This paper presents the effect of substrate thickness on horizontal magnetoresistance that detects the horizontal magnetic field perpendicular to bulk cross section area. The substrate thickness ( T ) concerns directly to the current density distribution and the effective depth ( t ) of current path corresponding to cross section area of current. The horizontal magnetoresistance depends on current distribution which concerns with substrate concentration, length, width and thickness of resistor. It changes by the effective depth of current path change by the unbalance between Lorentz’s force and Hall electrical force in vertical direction. From this study, the sensitivity of device increases with the thickness of substrate up to critical substrate thickness and still constant for thickness greater than this critical value. The current distribution is limited when substrate thickness less than a critical value and fully distributes when the thickness is greater than this value. At the same constant current, the longer length of resistor shows the lower current density which needs the longer effective depth of current which causes the critical substrate thickness to be increased accordingly.
Keywords: Lorentz force; Magnetic Field Sensors Techniques